Career networks and job matching: Evidence on the microeconomic foundations of human capital externalities - Daniel F. Heuermann (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2009)
Inspired by the literature on the importance of local career networks for the quality of labor market matches we investigate whether human capital externalities arise from higher job matching efficiency in skilled regions. Using two samples of highly qualified workers in Germany, we find that increasing the regional share of highly qualified workers by one standard deviation raises wages on the incidence of job change by up to three percent, pointing to the importance of improved job matching opportunities in human capital rich regions as a microeconomic source of human capital externalities. Evidence on regional differences in job change behavior suggests that human capital networks enable young workers to change jobs more easily and to thereby increase matching efficiency, which in turn reduces the overall number of job changes needed until an efficient match is reached. Benefits from improved matching opportunities predominantly arise from human capital networks enabling workers in skilled regions to change jobs within an industry and, thus, to capitalize on their industry-specific human capital.
Keywords: D62; J24; J31; R11; 330; Human Capital Externalities; Job Matching; Agglomeration Economies